HIV and the new viruses - Dalgleish, A. G. (Angus G.); Weiss, Robin (Academic, 1999)
HIV and the New Viruses presents cutting-edge reviews of persistent human virus infections as a coherent collection for the first time. These cover recently discovered viruses such as HHV-6, HHV-8 and HCV, as well as the latest research on HIV. This comprehensive and updated reference includes an in-depth study of the major issues in the epidemiology, pathogenicity, molecular virology, host responses and management of conditions associated with those viruses. Information on new pharmaceuticals and vaccine developments is also included. Edited by the leading experts in the field, HIV and the New Viruses will be essential reading for postgraduates, clinicians and researchers in virology, immunology, cancer, molecular biology and the pharmaceutical industry. Key Features * Presents cutting-edge reviews of persistent human virus infections as a coherent collection for the first time * Includes an in-depth study of the major issues in the epidemiology, pathogenicity, molecular virology, host responses, and management of conditions associated with those viruses.